2022
DOI: 10.3390/ijms232012151
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Physiological Effects of Browning Agents on White Adipocytes from Bone Marrow Mesenchymal Stromal Cells

Abstract: Two different types of adipose depots can be observed in mammals: white adipose tissue (WAT) and brown adipose tissue (BAT). The primary role of WAT is to deposit surplus energy in the form of triglycerides, along with many metabolic and hormonal activities; as thermogenic tissue, BAT has the distinct characteristic of using energy and glucose consumption as a strategy to maintain the core body temperature. Under specific stimuli—such as exercise, cold exposure, and drug treatment—white adipocytes can utilize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…MSCs (passage 3-4) were expanded according to the manufacturer's recommendation and incubated for 7 days with 20 nM of Irisin, we already demonstrated was effective in previous findings. 26 Specifically, we examined its impact on important biological parameters including cell survival, senescence, apoptosis, and DNA damage. By assessing these key parameters, we aimed to gain insights into the potential cellular responses to Irisin treatment and its influence on cellular viability, aging processes, programmed cell death, and DNA integrity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MSCs (passage 3-4) were expanded according to the manufacturer's recommendation and incubated for 7 days with 20 nM of Irisin, we already demonstrated was effective in previous findings. 26 Specifically, we examined its impact on important biological parameters including cell survival, senescence, apoptosis, and DNA damage. By assessing these key parameters, we aimed to gain insights into the potential cellular responses to Irisin treatment and its influence on cellular viability, aging processes, programmed cell death, and DNA integrity.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in a previous research we demonstrated the ability of Irisin to promote beiging of white adipocytes obtained from terminally differentiated cells. 26 However, it is essential for a safe and efficacious antiobesity medication to have minimal impact on the functionality of other cell types, especially stem cells, as they serve as a vital reservoir within the organism for maintaining tissue balance and homeostasis. When a drug reaches the WAT depots, its effects extend beyond mature adipocytes and impact various other cell types present within this tissue, such as MSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nociceptors may also be sensitized by T cells that release IL-17A and IFN-γ, which act at nerve terminals to increase neuropathic pain [ 113 ]. It has been shown, in recent years, that mesenchymal stromal cells (MSCs), which have the ability to differentiate into distinct mesenchymal cell lineages, including chondrogenic, adipogenic, and osteogenic lineages, [ 114 , 115 ], are able to modulate the inflammatory response through interleukin-10 (IL-10). During inflammation, different regulatory immune cells are induced, and their population is expanded.…”
Section: Immune Regulation Of Painmentioning
confidence: 99%
“…Furthermore, TRPV1 currents in DRG are inhibited by maresin 1, which reduces inflammatory pain [ 143 ]. Neither protectin D1 nor maresin 1 influence nociceptive mechanisms downstream of TRPA1 [ 115 , 145 ]. These results, when considered together, may open a new viewpoint towards the role of pro-inflammatory lipids, such as PGE2 and LTB4, in the activation of pain.…”
Section: Lipids Involved In Painmentioning
confidence: 99%